Curatorial Essays for the exhibition: Hestnes Ferreira: Forma | Matéria | Luz - Saraiva, A.; d'Almeida, P. Bento; Pinto, Paulo Tormenta (Curator: Alexandra Saraiva, Co-Curator: Patrícia Bento d'Almeida and Paulo Tormenta Pinto, MAC/CCB, Lisboa, 17 outubro 2024 - 13 abril 2025, 2024)
Hestnes Ferreira — Form | Matter | Light presents a reading of the work of architect Raúl Hestnes Ferreira (1931–2018) based on his working process, dominated by charcoal drawing and architectural experimentation. In Hestnes Ferreira’s deeply disciplined method, design decisions emerge in the heavy marks of steady charcoal strokes. Pure forms and classic typologies become entangled in this way of doing things, which is consolidated in a robust architecture that explores the qualities of materials in their natural expression, without filter or artifice. Hestnes Ferreira’s architecture achieves a sublime timelessness, whether through its formal simplicity or material expressiveness. In this context, space is the aggregating element, with the building being the foundation that gives it weight and proportion. Light and shadow are essential in this journey of abstraction, creating moments of singularity that merge inexorably in the experience of each place.